Region-dependent site conditions in China: Evidence from borehole data statistics - Yao, Xinxin; Zhang, Peng; Zhao, Yu; Wang, Hongwei; Wang, Daren (Frontiers in Earth Science, 2023)
Consideration of site effects is vital in modeling and predicting earthquake ground motions. In this study, profiles of 6179 boreholes were collected from four regions in China, i.e., the Capital Metropolitan (CM), Xinjiang (XJ), Guangdong–Guangxi (GG), and Sichuan–Yunnan (SY) areas. Quantitative characteristic parameters including site category, equivalent shear wave velocity (Vse), and the thickness of the overlying soil layer (H) defined by the Chinese seismic code, and VS30 and the median shear wave profile were all analyzed to confirm the dependency on site conditions among the four regions. Investigation revealed that the majority of sites in most regions are classified as Class-II sites with no Class-IV sites, except in CM. In comparison with the other three regions, a larger number of GG sites are classified as Class-I. Sites in XJ are generally characterized by small H values (<20 m) and large Vse values (250–450 m/s), while those in CM are characterized by large H values (average: ~50 m) and small Vse values (150–300 m/s). Generally, the Vse and H values are similar in GG and SY, i.e., the sites are covered by an overlying soil layer that is ~20m thick with an average Vse value of ~250 m/s. A very thin (<5 m) overlying soil layer is observed at many more sites in GG than at sites in the other three regions. The VS30 values in CM, SY, and GG all approximately follow a lognormal distribution with various logarithmic means, i.e., 257.2, 299.6, and 360.9 m/s, respectively. However, the VS30 values of most sites in XJ broadly follow a uniform distribution with a range of 200–550 m/s. We summarized the characteristics of the median VS profiles of each VS30-based category (C1, C2, and C3) for each region. The median VS profiles between any two regions are mainly manifested as parallel trends for sites in category C1, whereas they present trends of intersection for sites in categories C2 and C3. The findings of this study could serve as a basis for the establishment of a regional empirical model for site-dependent seismic response in China.